New Turner-Fairbank Alkali-Silica Reaction Susceptibility Test for Aggregate Evaluation. Issue 9 (September 2021) - Muñoz, Jose F.; Balachandran, Chandni; Arnold, Terence S.
The ASTM C1260 and ASTM C1293 are generally accepted as being the best available accelerated tests to evaluate the alkali-silica reactivity of aggregates used in concrete. Unfortunately, these tests have limitations, such as the significant amount of false-positive and false-negative results in ASTM C1260 and the alkali leaching in ASTM C1293, that reduce their accuracy. This paper introduces an alternative test method, the Turner-Fairbank alkali-silica reaction (ASR) susceptibility test (T-FAST) that overcomes traditional limitations of both ASTM standards. In the new test, the ASR was accelerated by exposing the aggregates to a 1 N NaOH solution, three different amounts of CaO, and two temperatures for 21 days. The reactivity index (RI), calculated based on the 21-day concentrations of aluminum, calcium, and silicon in liquid phase, was used to assess the alkali-silica reactivity of 24 well-known aggregates—17 coarse and 7 fine. The results agreed with the classification of the same based on ASTM C1293 and historic field performance available in the literature. The alkali levels at which the ASR reaction was triggered in a selection of aggregates were measured using the T-FAST experimental set up. The threshold alkali values obtained matched those previously reported using accelerated concrete expansion tests as well as with concrete blocks in outdoor exposure sites. The alkali threshold determined for a river sand from Arkansas helped to understand the unexpected ASR distress observed in the field for an aggregate traditionally categorized as nonreactive. This case is a good example of mismatch between the information obtained from accelerated-ASR standard tests and field performance.